ChemInform Abstract: Asymmetric Addition of Alkoxy Ethynyl Anion to Chiral N‐Sulfinyl Imines. Issue 10 (7th March 2013) - Verrier, Charlie; Carret, Sebastien; Poisson, Jean‐Francois
Abstract The addition of boron trifluoride reverses completely the diastereoselectivity [cf.(III) versus (VII)].